2010
DOI: 10.1111/j.1469-8749.2010.03838.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in white matter pathways in Angelman syndrome

Abstract: Aim  Angelman syndrome is a neurogenetic disorder characterized by severe intellectual disability, absent speech, seizures, and outbursts of laughter. The aim of this study was to utilize diffusion tensor imaging (DTI) to examine alterations in white matter pathways in Angelman syndrome, with an emphasis on correlations with clinical severity. Method  DTI was used to examine the arcuate fasciculus (AF), uncinate fasciculus (UF), inferior longitudinal fasciculus (ILF), inferior fronto‐occipital fasciculus (IFOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 26 publications
(51 reference statements)
5
53
0
Order By: Relevance
“…Abnormal, though identifiable, arcuate fasciculi have been reported in a range of disorders manifesting speech delay. [37][38][39] 42 reported a small frequency of the absence of the left arcuate fasciculus in healthy patients. In our control population, by contrast, all subjects had an identifiable left arcuate fasciculus.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal, though identifiable, arcuate fasciculi have been reported in a range of disorders manifesting speech delay. [37][38][39] 42 reported a small frequency of the absence of the left arcuate fasciculus in healthy patients. In our control population, by contrast, all subjects had an identifiable left arcuate fasciculus.…”
Section: Discussionmentioning
confidence: 99%
“…Peters et al (2004) also reported reduced myelination in the white matter of the brain. DTI tractography studies in participants with AS have also shown abnormalities in the arcuate fasciculus, inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, uncinate fasciculus, corticospinal tracts, and corpus callosum (Peters et al, 2011). The arcuate fasciculus is a white matter tract that connects the language comprehension region of the temporal lobe with the speech-generating region of the frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…They may precede the diagnosis [17,19] but are not absolutely specific [3,7,22]. Neuro-imaging studies may be normal but show global atrophy and abnormal myelination in the frontal lobes, as well as a thin corpus callosum [23,24], in approximately 60% of the cases [25]. This MRI finding is now an important feature in the evaluation and understanding of AS and may explain the language and motor difficulties observed in patients [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Epileptiform discharges tend to shift towards the frontal region [21] as observed in all cases, and reflect the functional neuro-chemical or maturational disorder of the frontal area: from a pathophysiological point of view as suggested by MRI [23,24,25,26], the mechanism could consist of delayed myelination, associated with a thin corpus callosum [23,26]. A previous study [27] using diffusion tensor imaging has demonstrated that in addition to delayed myelination, there was decreased axonal density and aberrant axonal organisation mainly in the temporal pathways, which partly explained the language, cognitive and social functioning disorders [26,27].…”
Section: Discussionmentioning
confidence: 99%